The romantic heritage in the theater Los conquistadores (1906) by José Santos Chocano - Ventura Vásquez, Williams Nicks (2021)
At the beginning of the 20th century, the literate sector and the popular crowd accepted the marvellous resonance of the descriptive and orchestral verses of José Santos Chocano y Gastañodi (1875-1934). As years passed, critics focused only on the superficiality and emphatic sonority of his compositions, leading to a massive lack of interest in the readers. It is not surprising, then, that his theatrical works have not been properly studied. In this sense, from an approach based on the manipulation of rhythm and theatrical semiology, we consider it important to review the play Los conquistadores (1906). The aim of this paper is to prove that Chocano does not improvise in the theatrical elaboration process of this historical drama, but rather he presents the romantic influences with a certain modernist attitude.